2022
DOI: 10.1109/tnsre.2022.3192761
|View full text |Cite
|
Sign up to set email alerts
|

Coil Efficiency for Inductive Peripheral Nerve Stimulation

Abstract: Magnetic stimulation of peripheral nerves is evoked by electric field gradients caused by high-intensity, pulsed magnetic fields created from a coil. Currents required for stimulation are very high, therefore devices are large, expensive, and often too complex for many applications like rehabilitation therapy. For repetitive stimulation, coil heating due to power loss poses a further limitation. The geometry of the magnetic coil determines field depth and focality, making it the most important factor that dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It can be found that the Joule heating is less than the reference full-sine, but the vibration energy is much larger. However, one peak of the optimized waveform might be obviously larger than the opposite peak if the Joule heating is taken as the optimization objective only [ 19 ].…”
Section: Optimization Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that the Joule heating is less than the reference full-sine, but the vibration energy is much larger. However, one peak of the optimized waveform might be obviously larger than the opposite peak if the Joule heating is taken as the optimization objective only [ 19 ].…”
Section: Optimization Results Discussionmentioning
confidence: 99%
“…To deal with the problem of coil heat, some scholars have improved the efficiency of stimulation by changing the coil structure such as modifying the geometry [ 19 ] or adding iron-core to reduce the heat generation [ 20 , 21 ]. In addition, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Axon polarization is dependent on the properties of the magnetic field (i.e., orientation to the axon, magnitude, and frequency), its geometry (i.e., axon radius, membrane thickness), and its electrical properties (i.e., conductivity, dielectric permittivity) [7]. The distance between the nerve and the coil plays a crucial role [8]. All of the above also depends on the characteristics of the magnetic field of the nerve itself, knowledge of which is the objective of this work.…”
Section: Discussionmentioning
confidence: 99%
“…A nerve has a electromagnetic field, which can be modified when another external electromagnetic field is applied in therapy. Numerous studies have been done to see if an electromagnetic pulse could regenerate injured peripheral nerves [1][2][3][4][5][6][7][8][9][10][11]. The results indicate that electromagnetic therapy increases the number of motor neurons to restore proper connections in the injured peripheral nerve [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…In order to simulate under the most realistic conditions possible, we conducted previous experiments with wires leading in and out of the coil [73]. However, we found that this approach leads to almost identical E-fields in the region of interest, and thus only increases the computation time unnecessarily.…”
Section: A Threshold Currentsmentioning
confidence: 99%